SWOT analysis for development strategy for Silamci natural tourism object facilities in Garut - Sucia, Mentari; Belasunda, Riksa (ARTEKS : Jurnal Teknik Arsitektur, 2024)
Natural tourism contributes significantly to GDP (gross domestic product) and is a major part of the Indonesian economy. In 2022, Indonesia ranked 32nd in the Travel and Tourism Development Index (TTDI), indicating a 3.6 percent rise in the GDP contribution of tourism. The adoption of the "new normal" during the COVID-19 epidemic led to the emergence of the road trip and micro tourism trends, in which travelers mostly select nearby locations that are accessible by private vehicle. Local visitors play a critical role in fostering the expansion of tourism in many locations. As a possible travel destination in Indonesia, Garut continues to attempt to diversify travel experiences by emphasizing amenities, accessibility, and attractions (3A). The tourist destination Silamci in Garut demonstrates how private ownership may have a big impact on an organization's ability to supply funding, infrastructure, and personnel as well as raise the standard of expert management. The objective of this study is to employ SWOT analysis to evaluate the state of the facilities as they stand and to identify areas for development. Through the results of field observations, interviews, questionnaire distribution, and comparison studies of related research items, qualitative methodologies were employed in the study. It was determined that enhancing the variety of facilities offered frequently constitutes the primary goal of Silamci's innovation development strategy. It is envisaged that enhancing the facilities' quality will serve as the cornerstone for raising Silamci's different values.